Study on Adoption of Chinnor Rice Production Technology and Constraints Faced by Farmers of Balaghat District, Madhya Pradesh - Khan, Mohammad Imran; Bisen, Uttam; Sarvade, S.; Gautam, Kamleshwar; Bisen, Sharad; Rai, S. K.; Shrivastava, Atul (International Journal of Bio-resource and Stress Management, 2021)
The Study was conducted during 2019–20 to find out the adoption of Chinnor rice production technology by farming communities of the Balaghat district, Madhya Pradesh, India. Farmers of an area were aware about technology invented by scientists of College of Agriculture, Balaghat. Adoption of interventions involved in given technology varied from 64–100%. Majority of the respondents respond to mixing of vermi-compost and other cakes in soil (77.72%), seed rate @ 20–25 kg ha-1 (69.40%), 2–3 times of ploughing (64.51%), recommended plant spacing (75.00%), organic manures for nutrient management (88.47%), mechanical method of weed control (94.96%), try biological control insect-pest (96.33%), manual harvesting as well as bagging method of storage (98.00%). Data indicates that the lodging of the crop due to height was the major constraint in their adoption and it ranks Ist as 68.33% respondents reported the problem of lodging. Long duration required for maturity of the Chinnor than other rice varieties was another limiting factor, ranked IInd with 61.67% farmers’ response, whereas less availability and high cost of pure seed of variety ranked IIIrd with 54.33% farmers’ response. Majority of respondents (36.33%) communicate with the scientists of the college and other institutions. With some improvements in qualitative parameters of the crop, adoption by farmers and yield of the crop will increase.